The role of the exemplary family in the formation of a happy family according to Islam - Adawiyah Ismail,; Rosma Aisyah Abd. Malek,; Jawiah Dakir,; Siti Rugayah Tibek,; Noor Aziah Mohd. Awal,; Fariza Md. Sham,; Salasiah Hanin Hamjah,; Rosmawati Mohamad Rasit, (Universiti Kebangsaan Malaysia, 2015)
The rise in family breakups are caused by the lack of knowledge about the role of the members in the family institution and about the guidance on family life through the exemplary family according to Islam. Hence, this study aims to identify the role of the exemplary family members in the formation of a happy family. The main method used in obtaining data in this paperwork is content analysis. The study has found that the understanding about the role of the mother, father as well as their children is very crucial nowadays due to the different challenges compared to the previous years. Exemplary family members who carry out their roles are able to form a happy family. Therefore, each family member should be knowledgeable about the exemplary family and the ways in forming a happy family based on the Quran and Sunnah. The implication is that an exemplary family which succeeds in creating a happy family is capable of enjoying life well and peacefully, setting the example to the general public and reducing unhealthy and undesirable activities in the society.